Study on Actual Energy Consumption for Evaporative Condenser in Ammonia Refrigerating Plants - Zhang Jianyi; Mi Wentao (Zhileng xuebao)
The energy consumptions for evaporative condensers with different brands and water - cooled condensers were analyzed by theoretical calculation, product selection calculation, and field tests. The results show that energy consumptions per kW heat rejection for evaporative condensers are nearly same for the calculations and field tests. The differences of the energy consumption are great among different brands of evaporative condensers at the same heat - rejection capacity. The energy consumption for the evaporative condenser of brand B is nearly twice that of brand A. Based on the field tests, the average energy consumption for the evaporative condensers with the three typical brands is approximately 32% that for the open water - cooled condensers and 47% that for the closed water - cooled condensers.